Prevalence and factors influencing drug-resistant tuberculosis in four regions of Ghana - Esther Ba-Iredire; James Atampiiga Avoka; Luke Abanga; Abigail Awaitey Darkie; Emmanuel Junior Attombo; Eric Agboli (PLoS ONE, 2025)
Introduction The alarming rate of drug-resistant tuberculosis (DR-TB) globally is a threat to treatment success among positive tuberculosis (TB) cases. Studies aimed at determining the prevalence, trend of DR-TB and socio-demographic and clinical risk factors contributing to DR-TB in the four regions of Ghana are currently unknown. This study sought to determine the prevalence and trend of DR-TB, identify socio-demographic and clinical risk factors that influence DR-TB, and analyse the relationship between underweight and adverse drug reactions and treatment outcomes among DR-TB patients in four regions of Ghana. Method It was a retrospective review conducted over 5 years, from January 2018 to the end of December 2022. The data were retrieved from the DR-TB registers and folders at the Directly Observed Treatment (DOT) centres in the four regions. Analysis of the data was conducted using STATA version 17. Results The prevalence of DR-TB in Ashanti was 10.1%, Eastern 5.3%, 27.8% in Central, and 2.7% in the Upper West region for the year 2022. The overall prevalence rate of DR-TB for the period 2018–2022 was 13.8%. The socio-demographic and clinical risk factors that influence DR-TB in the four regions are: age, marital status (aOR 3.58, P-value< 0.00, 95% CI 2.86–4.48), Senior High School (SHS) level of education (aOR 2.09, P-value = 0.01, 95% CI 1.21–3.63), alcohol intake (aOR 0.49, P-value <0.00, 95% CI 0.38–0.63), previously treated (aOR 22.03, P-value<0.00, CI 16.58–29.26), major adverse drug reaction (aOR 125.50, P-value<0.00, 95% CI 58.05–271.34), and minor adverse drug reaction (aOR 23.59, P-value<0.00, 95% CI 18.32–30.39); treatment outcome, cure (aOR 0.52, P-value<0.00, 95% CI 0.41–0.66), completed (aOR 9.67, P-value<0.00, 95% CI 6.56–14.28), relapsed (aOR 2.62, P-value = 0.01, 95% CI 1.33–5.18), Lost-to-Follow-up (LTFU) (aOR 0.45, P-value<0.00, 95% CI 0.29–0.70), and failure (aOR 35.24, P-value<0.00, 95% CI 7.76–159.99). Also, there was an association between underweight and adverse drug reaction (RRR 5.74, P-value<0.00, 95% CI 4.86–6.79) and treatment outcome (RRR 0.79, P-value<0.00, 95% CI 0.74–0.86). Conclusion The study shows that the prevalence of DR-TB in Ghana is low, probably not because the cases have reduced but due to inadequate GeneXpert machines to detect the cases. Age, marital status, education, alcohol intake, previously treated TB cases, adverse drug reactions, underweight, and treatment outcome are factors influencing the development of DR-TB. Therefore, interventions aimed at improving the nutritional status of DR-TB cases and minimising adverse drug reactions will improve treatment outcomes.